2010
DOI: 10.1063/1.3368706
|View full text |Cite
|
Sign up to set email alerts
|

High frequency magnetic field imaging by frequency modulated magnetic force microscopy

Abstract: High frequency ac magnetic field from magnetic recording head was successfully imaged by using our newly developed frequency-modulated magnetic force microscopy (FM-MFM), which uses the frequency modulation of cantilever oscillation caused by applying ac magnetic field to a mechanically oscillated cantilever. The FM-MFM has been demonstrated and the experimental results show good agreement with our proposed models for FM-MFM. The amplitude and phase images of an ac magnetic field can be obtained separately by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Therefore, techniques for detecting an alternating magnetic field with high spatial resolution are of great importance. Recently, Saito et al [11][12][13] reported the frequency modulation MFM (FM-MFM) technique and showed that it could achieve a spatial resolution of 15 nm. In FM-MFM, the first resonant frequency of the cantilever vibration f 1 is modulated by the alternating magnetic field with frequency f m , and magnetic signals are obtained using a heterodyne method with a modulated frequency of f 1 À f m .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, techniques for detecting an alternating magnetic field with high spatial resolution are of great importance. Recently, Saito et al [11][12][13] reported the frequency modulation MFM (FM-MFM) technique and showed that it could achieve a spatial resolution of 15 nm. In FM-MFM, the first resonant frequency of the cantilever vibration f 1 is modulated by the alternating magnetic field with frequency f m , and magnetic signals are obtained using a heterodyne method with a modulated frequency of f 1 À f m .…”
Section: Introductionmentioning
confidence: 99%
“…One solution for reducing this interference is to apply a phase-lock loop (PLL) circuit to maintain a constant frequency difference of f 1 À f m . 12,13 Another solution is to obtain the magnetic images using not f 1 but another resonant frequency such as the second resonant frequency. Recently, Venstra et al demonstrated Q-factor con-trol of a cantilever by mechanical sideband excitation at the sum (f 1 þ f 2 ) and difference (f 1 À f 2 ) frequencies.…”
Section: Introductionmentioning
confidence: 99%